Pendidikan Jual Beli Dalam Perspektif Islam - Yova murnika; Hanna sajiddah; Fitratul Mubaraq; Awaluddin Hidayat; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
People have been engaged in buying and selling for a long time and they range from very simple buying and selling practices to even buying and selling using complex tools that people have created from time to time. This article wants to emphasize that no matter how advanced the tools developed by humans are, business should be governed by mutually beneficial regulations. This paper is a literature study using three sources of data namely primary, secondary and tertiary data sources. This article describes the definitions of buying and selling, the legal basis of buying and selling in Korand, Hadith and scientific commentaries. This article also contains Islamic buying and selling principles and examples of buying and selling. By understanding the basic principles of buying and selling, we can be careful whether we are selling or buying goods.